Interplay between dietary nitrate metabolism and proton pump inhibitors: impact on nitric oxide pathways and health outcomes - Basaqr, Reem; Babateen, Abrar (Frontiers in Nutrition, 2025)
Proton-pump inhibitors (PPIs) are often-prescribed antacids that are useful in the treatment of gastrointestinal disorders. Nonetheless, a number of studies have raised concerns about their long-term use, linking them to a higher risk of cardiovascular disease and other possible adverse effects, including brain damage. Since nitric oxide (NO) plays a vital role in neurological and vascular health, it is important to look into how PPIs might change the NO pathway. Oral bacteria and the preservation of a healthy stomach environment are essential for the external pathway’s synthesis of NO, which involves dietary nitrates (NO₃−) and nitrites (NO2−). PPIs have been demonstrated to decrease stomach acidity, which decreases NO bioavailability and prevents dietary NO₃− from being converted to NO2− and, subsequently, to NO. Endothelial dysfunction, which is typified by decreased vasodilation and elevated vascular resistance—two major factors in the development of hypertension—may result from this drop in NO levels. Moreover, reduced NO levels are associated with impaired brain function since NO is necessary for maintaining cerebral blood flow, neuronal transmission, and overall cognitive functioning. We propose that PPIs influence nitrate metabolism by several potential mechanisms including PPI-induced hypochlorhydria and a change in oral and gastric microbiomes leading to dysbiosis. There may also be other contributing pathways. Understanding how PPIs impact the NO₃−-NO2−-NO pathway is crucial for assessing their long-term effects on cardiovascular and brain health. By comprehending this connection, we may more effectively weigh the potential systemic risks of PPIs against their therapeutic advantages for gastrointestinal disorders. This may also guide safer prescription practices and patient management measures.